Can the Dunning-Kruger effect occur in the motor performance domain? - Tremayne, Kell S.; Newbery, Glenn; Tremayne, Patsy; Nolan, Kenneth A. (International Journal of Sport & Exercise Psychology, 2022)
The Dunning-Kruger effect is commonly understood as the tendency of relatively poor performers to grossly overestimate their ability and performance. This effect has been observed in a number of domains for which competence is wholly dependent on domain specific knowledge (e.g., the academic domain; the medical domain). However, it is claimed that the motor performance domain is not susceptible to the Dunning-Kruger effect because competence in this domain is dependent on factors other than knowledge (e.g., physical skill). The present study aims to test this claim. Eighty-three male participants performed one trial of the hand-grip strength task using their dominant hand. They also estimated their relative ability on the task, their relative performance on the task, and their score on the task. Participants were split into quartiles based on their actual task score. For each quartile, the mean estimated ability percentile and the mean estimated performance percentile were compared to the mean actual task score percentile. Also, mean estimated task score and mean actual task score were compared across quartiles. Consistent with the typical Dunning-Kruger effect, it was found that the worst performers were the most miscalibrated and significantly overestimated themselves, whereas the best performers significantly underestimated themselves. These findings indicate that the Dunning-Kruger effect can occur in the motor performance domain. They also cast doubt on the adequacy of the "metacognitive deficit" explanation, suggesting instead that, in the motor performance domain, motivational biases and defenses play a key role in the Dunning-Kruger effect.